PENGARUH PERAN JOB SATISFACTION DALAM MEMEDIASI FLEXIBLE WORKING ARRAGEMENTS TERHADAP EMPLOYEE PERFORMANCE PASCA PANDEMI COVID-19 DI PT. BPR MITRA BALI MANDIRI MENGWI BADUNG - Ni Putu Monica Puspitasari; Ni Made Yudhaningsih; I Kadek Donny Wishanesta (Yayasan Nusantara Hasana Berdikari, 2023)
The Covid-10 pandemic has made all the business world sink without exception so that the country's economy has become unstable, due to the absence of economic development, customers are even competing to withdraw their funds at the Bank for daily needs due to restrictions on being prohibited from leaving the house by the government to limit the transmission of the virus. As a result, the banking world has also collapsed and we have to look for other efforts, one of which is to implement work from home, with flexible work to create job satisfaction so that performance can be improved even though it is not like the normal days before Covid-19. This was also carried out by PT. BRP Mitra Bali independently in an effort to run the company's business from adversity. This research was conducted at PT. BPR. Mitra Bali Bandiri with the title The Influence of the Role of Job Satisfaction in Mediating Flexible Working Arrangements on Employee Performance Post the Covid-19 Pandemic at BPR. Mitra Bali Mandiri. This research uses an associative research design type with quantitative research methods, with research techniques carried out by interviews, distributing questionnaires, documents and literature, as well as using classical assumption tests and simple linear regression tests which are tested with the help of the IBM SPSS Statistics 26 computer program. Results from research obtained that (1). Flexible Working Arragements (Flexible Work) has a positive and significant effect on Employee Performance. The results of this study indicate that (2). Flexible Working Arragements have a positive effect on Job Satisfaction, (3). Flexible Working Arragements Job Satisfaction have a positive and simultaneous effect on Employee Performance (4). Working Arragements through Job Satisfaction on Employee Performance has a positive and simultaneous influence either individually or together, both directly and indirectly on PT. BPR. Mitra Bali Mandiri .